Volume 8: Mechanics of Solids, Structures and Fluids; Vibration, Acoustics and Wave Propagation 2011
DOI: 10.1115/imece2011-63591
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Injection Molding Parameters on Mechanical Properties of Low Density Polyethylene Filled With Multiwalled Carbon Nanotubes

Abstract: In this paper, we investigated the effect of injection molding parameters such as melt temperature, mold temperature, injection speed and holding pressure on the mechanical properties of low density polyethylene reinforced with 2.5 wt% multi-walled carbon nanotubes. The Taguchi methodology with four factors and two levels was used for the design of the injection molding experiments. The mechanical properties were evaluated by tensile tests in the flow direction at room temperature (23 °C) at crosshead speeds o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…For example, an LDPE sample (Braskem) reportedly has MFI = 30 g/10 min and a modulus of 80 MPa . We report a 155 MPa modulus for LDPE with MFI = 1.1 g/10 min, and an LDPE sample (ARPECHIM) with MFI = 2.02 g/10 min has been reported as having a modulus of 200 MPa . These results suggest that Rusu et al may have reported a neat LDPE modulus significantly below its true value, which would provide an explanation for the extraordinarily large percentage enhancements in modulus they reported with lignin addition.…”
Section: Resultsmentioning
confidence: 48%
See 1 more Smart Citation
“…For example, an LDPE sample (Braskem) reportedly has MFI = 30 g/10 min and a modulus of 80 MPa . We report a 155 MPa modulus for LDPE with MFI = 1.1 g/10 min, and an LDPE sample (ARPECHIM) with MFI = 2.02 g/10 min has been reported as having a modulus of 200 MPa . These results suggest that Rusu et al may have reported a neat LDPE modulus significantly below its true value, which would provide an explanation for the extraordinarily large percentage enhancements in modulus they reported with lignin addition.…”
Section: Resultsmentioning
confidence: 48%
“…70 We report a 155 MPa modulus for LDPE with MFI = 1.1 g/10 min, and an LDPE sample (ARPECHIM) with MFI = 2.02 g/10 min has been reported as having a modulus of 200 MPa. 71 These results suggest that Rusu et al 36 may have reported a neat LDPE modulus significantly below its true value, which would provide an explanation for the extraordinarily large percentage enhancements in modulus they reported with lignin addition.) Hu et al 49 produced HDPE composites with 20 wt % lignin by melt mixing and reported a 15% increase in Young's modulus relative to neat HDPE, from 502 to 577 MPa.…”
Section: ■ Results and Discussionmentioning
confidence: 86%
“…Generally, dissolving of the resin takes place on account of the frictional heat from the screw pivot inside the barrel. In a study by Fetecau et al [131], the effects of melt temperature, mould temperature, holding pressure and injection speed on properties of low-density polyethylene reinforced with 2.5 wt% multi-walled carbon nanotubes were assessed. The study showed melt temperature as the most significant factor affecting elastic modulus.…”
Section: Temperaturementioning
confidence: 99%